What Have Religious Groups Done After 3.11? Part 2: From Religious Mobilization to "Spiritual Care". Issue 8 (5th August 2013) - McLaughlin, Levi
Abstract : Buddhist, Christian, Shinto, and other religious responses to devastation in the wake of the March 2011 earthquake, tsunami, and nuclear disasters in northeast Japan have included a great deal more than providing material aid and seeing to the ritual needs of the dead and the bereaved. This article considers ways in which burgeoning collaborations of religious professionals, clinical care workers, and academics are crafting a public persona of religion as "spiritual care, " a new formulation designed to meet the needs of a Japanese public that welcomes therapeutic interventions for disaster victims yet remains leery of religion. While the move from the religious to the spiritual presents novel opportunities to rehabilitate Japanese religion's public image, it appears as if some post‐disaster religious initiatives challenge definitions of what "religion" may include. These initiatives also pose open questions about how Japanese religious institutions and practices may change as they adapt to the priorities of a public in need of help but ill‐disposed toward religion.